Graphene for field emission cathode and preparation method thereof
The preparation process of graphene is simplified by the laser direct writing method, and the problems of complex graphene preparation and poor field emission performance in the prior art are solved, thereby achieving more efficient graphene preparation and excellent field emission performance.
Patent Information
- Application Number
- CN202411738340.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, the preparation of graphene by chemical vapor deposition method has problems such as complex preparation process, long cycle, high environmental requirements and large opening field strength, which affects the field emission performance and industrial production of graphene.
Graphene is produced by direct laser writing method, and the PI film is ablated by carbon dioxide laser, which simplifies the preparation process, reduces the opening field strength, and increases the maximum current density and field enhancement factor.
It realizes efficient preparation of graphene, with smaller opening field strength, larger maximum current density, and larger field enhancement factor, significantly improving field emission performance.
Smart Images

Figure CN119797343A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of field emission cathode materials, in particular to graphene for field emission cathode and a preparation method thereof. Background Art
[0002] Field emission refers to the phenomenon that electrons are emitted from the surface of a solid under the action of a strong electric field. Good cathode materials will make it easier for electrons to be emitted and the emission process more stable. The main application areas of field emission include: (1) Displays: Field emission displays (FEDs) have the characteristics of high brightness, high contrast and wide viewing angle, and are a new type of flat-panel display. (2) Electron sources: In the fields of electron microscopes and electron probes, field emission as an electron source can provide high-energy electron beams for material analysis and processing. (3) Vacuum electronic devices: Such as vacuum microelectronic devices and cold cathode devices, field emission is used as an electron emission source in these devices, and has the advantages of low energy consumption and high efficiency.
[0003] Graphene is a sp 2 The new type of nanocarbon with a two-dimensional structure of a carbon grid has excellent electrical, thermal and mechanical properties and abundant electron tunneling edges, making it a good material for a field emission cathode. There are many methods for preparing graphene, including mechanical exfoliation, redox method, electrophoresis, chemical vapor deposition, etc. Among them, mechanical exfoliation, redox method, and electrophoresis method have disadvantages such as low yield, poor controllability of the preparation process, and difficulty in electronic integration. In contrast, chemical vapor deposition is an effective method for large-area, low-cost preparation of graphene. The process of preparing graphene by traditional chemical vapor deposition is as follows: Figure 1As shown. First, the copper foil is cut into a certain size as a graphene growth substrate. In order to remove surface impurities and oxides, the copper foil is soaked in glacial acetic acid, acetone, isopropanol and deionized water for 5 minutes respectively. The treated copper foil is placed in a quartz tube in the middle of the heating zone of the tube furnace, and is rapidly heated to 1030°C in an atmosphere of 300sccm (1sccm=1mL / min) Ar and a certain flow of H2. The temperature is maintained for 30 minutes, and then CH4 is introduced for graphene growth. According to the different morphologies of the grown graphene, the flow rates of CH4 and H2 and the growth time can be adjusted as needed. After the graphene growth is completed, the introduction of H2 and CH4 is stopped, and the tube furnace is cooled to room temperature. The grown graphene is transferred from the copper foil to the silicon wafer substrate containing the oxide layer using a wet transfer assisted by polymethyl methacrylate (PMMA) to complete the preparation. Most researchers prepare graphene by chemical vapor deposition, that is, first use the above-mentioned traditional method to prepare graphene with various morphologies such as single-layer graphene film, graphene island, and graphene with buffer layer, and then explore the influence of graphene's morphological characteristics on its field emission performance. The experimental results show that compared with single-layer graphene film, the turn-on field strength of graphene island and graphene with buffer layer is reduced by about 6V / μm, and the maximum field emission current density is also improved, which is also the best result of most groups' research. However, no matter how to regulate, the preparation of graphene by chemical vapor deposition has always had the problems of complex preparation process, long cycle, high environmental requirements, and large turn-on field strength of the prepared graphene, which greatly affects the field emission performance and industrial production of graphene. Summary of the invention
[0004] In order to solve the deficiencies in the prior art, the present invention provides a graphene for field emission cathode and a preparation method thereof. Compared with the production of graphene by laser direct writing method, the present invention has a simple preparation process and a short cycle. In addition, the graphene prepared by the present invention has a smaller opening field strength, a larger maximum current density, and a larger field enhancement factor. That is, while the preparation method is convenient, the field emission performance is also better.
[0005] In order to achieve the above object, the specific scheme adopted by the present invention is: On the one hand, the present invention provides a method for preparing graphene for field emission cathode, which mainly comprises the following steps: S1. Provide a PI film with a thickness of 0.1 to 0.15 mm, and place the PI film on a laser induction device. S2. The preset laser power is 7.2-10.8 W, the scanning speed is 300 mm / s, and the PI film is ablated by laser direct writing to prepare graphene.
[0006] Furthermore, the thickness of the PI film is 0.125 mm and the laser power is 7.2 W.
[0007] Furthermore, graphene has an upright fibrous structure with a three-dimensional tip emission morphology.
[0008] Furthermore, the graphene field emission motor can simultaneously obtain a power of more than 2×10 4 μA / cm 2 The current density and 10 4 The stability field enhancement factor is orders of magnitude.
[0009] On the other hand, the present invention provides a graphene for a field emission cathode, which is prepared by the above method.
[0010] Beneficial effects:
[0011] (1) The present invention adopts laser direct writing technology to prepare graphene by ablating PI film with a carbon dioxide laser, and applies this technology to the field of field emission for the first time. By irradiating the surface of the PI film with laser, heat accumulation causes the local surface temperature to rise rapidly. The local high temperature destroys the CO, C=O and NC bonds of the PI film and causes CO, C2H2 and other gases to escape. These gases are conducive to isolating oxygen, reducing oxidation and forming a fibrous structure. When the aromatic groups are reorganized, sp 3 Hybridized carbon atoms are converted to sp 2 Hybridized carbon atoms form the basic structure of graphene.
[0012] (2) The present invention has an emission current density of 10 μA / cm 2 When the power is 7.2W, the graphene prepared can obtain a turn-on field strength of 0.272V / μm, and an ultra-high field enhancement factor of 14391 is obtained in the field emission experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a process diagram for preparing graphene using chemical vapor deposition in the prior art.
[0014] Figure 2 This is a process diagram of preparing graphene by laser direct writing in the present invention.
[0015] Figure 3 These are the Raman images of the samples obtained in Examples 1-12 and Comparative Examples 1-6.
[0016] Figure 4 These are SEM images of graphene samples prepared in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5.
[0017] Figure 5 It is a JE characteristic curve diagram of the graphene samples prepared in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5.
[0018] Figure 6 These are FN diagrams of the graphene samples prepared in Example 2, Example 5, Example 8, Example 11, Comparative Example 2, and Comparative Example 5. DETAILED DESCRIPTION
[0019] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] The present invention provides a graphene field emission cathode and a preparation method thereof, please refer to Figure 2 , and its preparation method mainly comprises the following steps: S1. Provide a PI film with a thickness of 0.1 to 0.15 mm, and place the PI film on a laser induction device. S2. The preset laser power is 7.2-10.8 W, the scanning speed is 300 mm / s, and the PI film is ablated by laser direct writing to prepare graphene.
[0021] Example 1
[0022] A method for preparing graphene for a field emission cathode mainly comprises the following steps:
[0023] S1. Provide a PI film with a thickness of 0.1 mm and place the PI film on a laser induced device.
[0024] S2, preset laser power to 7.2W, scanning speed to 300mm / s, use laser direct writing to ablate PI film to prepare graphene.
[0025] Example 2
[0026] The difference between Example 2 and Example 1 is that in step S1, the thickness of the PI film is 0.125 mm.
[0027] Example 3
[0028] The difference between Example 3 and Example 1 is that in step S1, the thickness of the PI film is 0.15 mm.
[0029] Example 4
[0030] The difference between Example 4 and Example 1 is that in step S2, the laser power is 8.4W.
[0031] Example 5
[0032] The difference between Example 5 and Example 2 is that in step S2, the laser power is 8.4W.
[0033] Example 6
[0034] The difference between Example 6 and Example 3 is that in step S2, the laser power is 8.4W.
[0035] Example 7
[0036] The difference between Example 7 and Example 1 is that in step S2, the laser power is 9.6W.
[0037] Example 8
[0038] The difference between Example 8 and Example 2 is that in step S2, the laser power is 9.6W.
[0039] Example 9
[0040] The difference between Example 9 and Example 3 is that in step S2, the laser power is 9.6W.
[0041] Example 10
[0042] The difference between Example 10 and Example 1 is that in step S2, the laser power is 10.8W.
[0043] Embodiment 11
[0044] The difference between Example 11 and Example 2 is that in step S2, the laser power is 10.8W.
[0045] Example 12
[0046] The difference between Example 12 and Example 3 is that in step S2, the laser power is 10.8W.
[0047] Comparative Example 1
[0048] The difference between Comparative Example 1 and Example 1 is that in step S2, the laser power is 4.8W.
[0049] Comparative Example 2
[0050] The difference between Comparative Example 2 and Example 2 is that in step S2, the laser power is 4.8W.
[0051] Comparative Example 3
[0052] The difference between Comparative Example 3 and Example 3 is that in step S2, the laser power is 4.8W.
[0053] Comparative Example 4
[0054] The difference between Comparative Example 4 and Example 1 is that in step S2, the laser power is 6.0W.
[0055] Comparative Example 5
[0056] The difference between Comparative Example 5 and Example 2 is that in step S2, the laser power is 6.0W.
[0057] Comparative Example 6
[0058] The difference between Comparative Example 6 and Example 3 is that in step S2, the laser power is 6.0W.
[0059] Comparative Example 7
[0060] The difference between Comparative Example 7 and Example 1 is that in step S1, the film thickness of the PI film is 0.05 mm.
[0061] Comparative Example 8
[0062] The difference between Comparative Example 8 and Example 1 is that in step S1, the film thickness of the PI film is 0.075 mm.
[0063] Comparative Examples 7 and 8 have thin PI films that are easily curled when heated, and the samples are punctured when the power is too large, resulting in poor uniformity of the prepared samples. Subsequent performance analysis will not analyze Comparative Examples 7 and 8.
[0064] The samples prepared in Examples 1-12 and Comparative Examples 1-6 were tested by Raman spectroscopy. Figure 3 As shown in the figure, all samples showed the three intrinsic peaks of graphene (D peak, G peak, 2D peak), proving that graphene was indeed generated by laser direct writing. -1 The D peak at 1580 cm indicates the disorder and defect degree of vertical graphene and is considered to be the disorder vibration peak of vertical graphene. -1 The G peak at indicates the formation of graphitized structure and is considered to be the characteristic peak of vertical graphene. D / I G The intensity ratio indicates the degree of defects in graphene. The smaller the ratio, the fewer defects, the more perfect the crystallization, and the higher the quality. -1 The 2D peak at is generally related to the number of graphene layers and is usually expressed as I 2D / I G The intensity ratio represents the number of graphene layers. The larger the ratio, the fewer the layers.
[0065] We conducted Raman tests on each group of samples at three different locations. The Raman spectra of the samples prepared in all embodiments and comparative examples have high D peaks. High D peaks indicate that graphene has more defects and edges, indicating that amorphous carbon is easily accumulated at the bottom and surface of the prepared graphene samples. In addition, the 2D peak of each group of samples is very low, indicating that the graphene sheet is a multilayer structure. The I peaks of the graphene prepared in Examples 1-12 and Comparative Examples 1-6 are as follows: D / I G The values are shown in Table 1.
[0066] Table 1 I of samples obtained from Examples 1-12 and Comparative Examples 1-6 D / I G value Film thickness / mm Laser power / W <![CDATA[I D / I G value]]> Example 1 0.1 7.2 0.993 Example 2 0.125 7.2 0.845 Example 3 0.15 7.2 1.136 Example 4 0.1 8.4 0.972 Example 5 0.125 8.4 0.705 Example 6 0.15 8.4 1.158 Example 7 0.1 9.6 1.012 Example 8 0.125 9.6 0.886 Example 9 0.15 9.6 1.323 Example 10 0.1 10.8 1.061 Embodiment 11 0.125 10.8 0.844 Example 12 0.15 10.8 1.251 Comparative Example 1 0.1 4.8 0.979 Comparative Example 2 0.125 4.8 0.827 Comparative Example 3 0.15 4.8 1.120 Comparative Example 4 0.1 6.0 0.969 Comparative Example 5 0.125 6.0 0.796 Comparative Example 6 0.15 6.0 1.136
[0067] From Table 1, we can see that for the same group of data at the same power, when the thickness of the film is 0.125mm, the ratio of the D peak to the G peak is lower than that of the other groups, that is, the graphene has fewer defects and edges, better quality, and is more beneficial to the subsequent experiments. Therefore, we finally chose the 0.125mm thick PI film as the substrate for subsequent experiments.
[0068] The surface morphologies of the samples prepared in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5 were characterized on a 0.125 mm PI film using SEM. Figure 4 As shown. It is observed that the graphene prepared in Comparative Example 2 (under the condition of lower power, i.e. 4.8w laser power) is in the form of foam; the graphene prepared in Comparative Example 5 (under the condition of medium power, i.e. 6w laser power) is in the form of upper fiber and lower foam; the graphene prepared in Example 2 (under the condition of higher power, i.e. 7.2w laser power) is in the form of upright fiber; the graphene prepared in Examples 5, 8 and 11 are all in the form of vertical fiber, which is similar to the structure of the graphene prepared in Example 2, i.e. when the laser power is greater than 7.2w, the morphology of the prepared graphene is basically fixed. This is because the physical formation of graphene follows the process of fluid dynamics. When the laser radiation energy increases, the carbon-containing substrate will change from the lamellar graphene structure to the nanofiber shape.
[0069] Field emission refers to the phenomenon that electrons are released from the cathode surface under the action of a strong electric field, which belongs to cold cathode emission. The free electrons in the metal need to do a certain amount of work to escape from the metal, which is called the work function of the metal. Therefore, free electrons usually move in a certain electron potential well in metal conductors. When the metal acts as the cathode and a certain voltage is applied between the anode and the cathode, a certain potential barrier is formed on the cathode surface; when the applied voltage is large, the width of the barrier decreases, and the free electrons can be released from the metal through the quantum effect of barrier penetration. The emission phenomenon was first discovered in 1897. However, the theoretical model of field emission was not derived until 1928 by RH Fowler and LW Nordheim based on the free electron theory and quantum tunneling effect of metal materials. Based on this theory, they derived the Fowler-Nordheim equation (FN equation for short), successfully establishing a functional relationship between the current density of field emission, the work function of the material, and the strength of the external electric field, laying a theoretical foundation for subsequent research on field emission.
[0070] According to the FN formula: Where E is the average electric field between the anode and cathode plates, J is the current density, and A = 1.5414 × 10 - 6 AHr -2 , B=6.83×10 3 eV -3 / 2 Vμm -1 , the work function φ is determined by the energy band structure of the material itself, which is the Fowler-Nordheim formula. 2 Moving to the left side of the equation and taking the logarithm of both sides, we get the following formula:
[0071] This gives ln(J / E 2 ) and 1 / E, namely the FN curve, the two are linearly related, and the slope K of the curve is related to the field enhancement factor β and the work function φ. Then, the field enhancement factor β can be obtained by calculating the slope of the FN curve, and the size of β is:
[0072] In the FN curve, ln(J / E 2 ) and 1 / E are linearly related, and this relationship and the field enhancement factor are used together to evaluate the field emission performance of the material.
[0073] Field emission performance tests were conducted on some samples. During the field emission test, indium tin oxide (ITO) coated glass was used as the anode, and the vertical graphene with metal copper foil as the substrate was fixed on the stainless steel plate with conductive tape as the cathode, and connected to a high-voltage DC power supply to provide negative high voltage. The size of all test samples is a circle with a diameter of 1 cm, and the distance between the cathode and the anode is 5 mm. After fixing the sample (the sample is fixed by wiping the back of the sample clean, fixing it on the cathode plate of the field emission with conductive tape, and then folding the conductive tape upward to connect it to the graphene prepared on the front of the sample, so that the graphene and the cathode plate form a conductive path), start the vacuum pump group. When the vacuum is drawn to 5×10 -4 When the pressure is below 100 Pa, the field emission characteristic test is carried out. During the test, the distance between the two electrodes remains unchanged, and the voltage between the two electrodes is adjusted to gradually increase from zero, so that a current is generated between the two electrodes and gradually increases, and the voltage and current signals are recorded.
[0074] Defined current density reaches 10μA / cm 2 The corresponding field strength is the turn-on electric field, and the field emission JE characteristic curves of the graphene obtained in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5 are as shown in Figure 5 As shown in the figure, it can be clearly seen from the comparison that the maximum current density of the graphene prepared in Example 2 is higher than that of the other groups, and the maximum current density is 26242.04 μA / cm 2 The opening electric field is 0.272 V / μm, which is lower than that of the other groups. The reason is that compared with the samples prepared in Comparative Examples 2 and 5, the sample prepared in Example 2 begins to have an upright fibrous structure with sharp emission sites, which is conducive to electron emission.
[0075] Taking into account the particularity of the graphene structure, including the two-dimensional structure of graphene and the three-dimensional structure of carbon fiber, a composite conductive network will be formed, which increases the electron transmission channel between graphene and the electrode, and graphene itself has ultra-high conductivity, so the structure can effectively improve the conductivity between graphene and the electrode, and improve the field emission performance of the device. Therefore, the present invention measures the conductivity of the samples obtained in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5. The opening field strength, maximum current density, conductivity and resistivity of each group are shown in Table 2.
[0076] Table 2 Turn-on field strength, maximum current density, conductivity and resistivity of graphene obtained in some examples and comparative examples
[0077] As shown in Table 2, the opening field strength of Comparative Example 2 and Comparative Example 5 is relatively high. The reason for this phenomenon is that these two groups of samples are still close to the two-dimensional plane morphology, and their emission electrons reach 10μA / cm 2 The current density requires a higher voltage, and without a sufficient number of field emission tips, it is difficult to obtain a larger current density. The sample in Example 2 has the highest current density while having the highest conductivity and the lowest resistivity, which fully demonstrates that the large current density is inseparable from the excellence of its electrical properties. As the laser power continues to increase, the fibrous structure does not undergo an essential change, but because the fiber density will increase, the screen effect will cause certain obstacles, resulting in the turn-on field strength not continuing to decrease, and the current density will not increase indefinitely, but tend to stabilize. By comparison, it can be observed that as the laser power continues to increase, the turn-on field strength will continue to decrease, and the maximum current density will continue to increase, but will eventually stabilize within a certain range, so the laser needs to be controlled within a reasonable range. Too high or too low will affect the size of its turn-on field strength.
[0078] The FN diagrams of the graphene samples obtained in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5 are as follows: Figure 6 As shown, the field enhancement factor β can be calculated by combining formula (3). The field enhancement factors of the samples prepared in Example 2, Example 5, Example 8, Example 11, Comparative Example 2 and Comparative Example 5 are shown in Table 3.
[0079] Table 3 Field enhancement factors of graphene obtained from some examples and comparative examples Field Enhancement Factor Example 2 14391 Example 5 12808 Example 8 11978 Embodiment 11 11149 Comparative Example 2 5304 Comparative Example 5 6270
[0080] It can be seen from Table 3 that the field enhancement factors prepared in the embodiments of the present invention are 11149-14391, and the field enhancement factor of the sample prepared in Example 2 is significantly increased, which is attributed to the morphological structure of the fibrous graphene and its high density on the substrate.
[0081] Through the above analysis, it can be concluded that when the laser power is large enough, fibrous graphene will be induced, which has a three-dimensional tip emission morphology and excellent field emission performance. In addition, the laser power needs to be controlled within a suitable range. Too high or too low will affect the field emission performance of graphene.
[0082] At the same time, in the existing research, the present invention compares the turn-on field strength, maximum current density and field enhancement factor of the cathode materials commonly used in the prior art (graphene and carbon fiber prepared by conventional methods) and the graphene prepared by the present invention, and the results are shown in Table 4.
[0083] Table 4 Turn-on field strength, maximum current density and field enhancement factor results of graphene, carbon fiber prepared by conventional methods and graphene prepared by the present invention Opening field strength / V / μm <![CDATA[Maximum current density / μA / cm 2 > Field Enhancement Factor Graphene in the prior art 5.55-7.95 7.3-40.3 336-1605 Carbon fiber in the prior art 0.95-1.74 960-1410 9880-19856 Graphene prepared by the present invention 0.272-0.320 18955-26242 11149-14391
[0084] As shown in Table 4, the best turn-on field strength of graphene prepared by conventional methods is basically 5.0-7.0 V / μm, the maximum current density is also small, and the field enhancement factor is usually 10 3 The field emission performance of carbon fiber is better than that of graphene. The graphene prepared by the present invention can simultaneously obtain a field intensity higher than 2×10 4 μA / cm 2 The current density and 10 4 The stable field enhancement factor is of an order of magnitude, so the graphene prepared by the present invention has good field emission characteristics.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing graphene for field emission cathode, characterized in that: The main steps are as follows: S1. Provide a PI film with a thickness of 0.1~0.15mm and place the PI film on the laser induction device. S2, preset laser power is 7.2~10.8W, scanning speed is 300mm / s, and laser direct writing is used to ablate PI film to prepare graphene.
2. The method for preparing graphene for field emission cathode according to claim 1, characterized in that: The thickness of the PI film was 0.125 mm and the laser power was 7.2 W.
3. The method for preparing graphene for field emission cathode according to claim 2, characterized in that: The graphene field emission cathode has an upright fibrous structure and a three-dimensional tip emission morphology.
4. The method for preparing graphene for field emission cathode according to claim 2, characterized in that: The graphene field emission motor can simultaneously obtain a power of more than 2×10 4 μA / cm 2 The current density and 10 4 The stability field enhancement factor is orders of magnitude.
5. A graphene for field emission cathode, characterized in that: The method is prepared by the method described in any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of patterned graphene conductive thin film
CN103236295A
Preparation method of polyimide / graphene composite material and product of material
CN104194335A
Method and apparatus for continuously preparing porous graphene film
CN107739027A
Laser engraving preparation method of high-conductivity graphene film array
CN109421402A
Laser induced graphene hybrid materials for electronic devices
US20190088420A1